Potencialidade de utilização de liquens como bioindicadores do histórico de incêndios no Parque Nacional Serra de Itabaiana/SE - Santos, Ingride Natane Miguel (2022)
Forest fires in the Serra de Itabaiana/SE National Park (PARNASI) occur practically every year, these events are the result of anthropic actions, according to the park's management plan, tourism, vandalism and agriculture stand out due to the use and land occupation. Such actions impact the dynamics of the landscape, especially in the research area, the savanna formation (cerrado). The main objective of the research was to identify the potential of lichens of the Cladoniaceae family for bioindication of the history of forest fire in the natural open formation landscape unit in the Serra de Itabaiana National Park - Sergipe. We sought to test the hypothesis of the distribution pattern of lichens, mainly those of the Cladoniaceae family, which could be shown as potential bioindicators of the occurrence of forest fires in areas of natural open formations. Based on a theoretical framework dealing with forest fires and the impacts on landscape dynamics, the lichen of the Cladoniaceae family as a potential bioindicator and the dynamic process of the park landscape in a post-fire scenario. In the methodology, it characterizes the study area, presents the method and procedures used in the research. For data analysis, a survey of fire scars was carried out with a temporal cut of 1985-2020 following the methodology of MapBiomas Fogo, and with the accomplishment of the projective interview with manager and brigadistas, using the PARNASI location map for temporal location of events of fires, in order to validate the role of lichens of the Cladoniaceae family as a bioindicator of fires in the park. The occurrence of lichens of the Parmeliaceae family in the area of fire occurrence in PARNASI had a significant percentage, as well as in areas where there was no record of fires, corroborating the bioindicator potential of forest fires in the park and to monitor areas with possible anthropic disturbances. Lichen, being an organism extremely sensitive to environmental changes, is able to bioindicate such events so that it can recover areas that were taken by fire.